2023
DOI: 10.18240/ijo.2023.08.17
|View full text |Cite
|
Sign up to set email alerts
|

Exploring multi-level risk factors and post-war burdens of trachomatous trichiasis among displaced population in Raya Kobo districts, implication for urgent action

Abstract: AIM: To estimate post-war burdens of trachomatous trichiasis (TT) and multi-level risk factors among displaced population in Raya Kobo districts, implication for urgent action. METHODS: A community-based cross-sectional study was conducted among 603 participants from randomly selected 14 displaced slums in the Raya Kobo district. The data was collected from February 16th to March 30th, 2023. Study participants were selected using the multistage sampling technique. A structured questionnaire and ophthalmic loup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…Despite growing recognition of the detrimental effects of conflict on maternal and child healthcare, the literature is bereft of studies robustly quantifying the association between conflict and TT protective dose uptake of pregnant women during ANC service in Ethiopia, particularly in the Amhara region ( 8 , 9 ). The continued civil war in Ethiopia, specifically in the Amhara region, has led to extensive damage to healthcare facilities, disrupting maternal health services for more than 70,000 pregnant women, causing 1.4 million displacements and 600,000 reported deaths ( 11 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite growing recognition of the detrimental effects of conflict on maternal and child healthcare, the literature is bereft of studies robustly quantifying the association between conflict and TT protective dose uptake of pregnant women during ANC service in Ethiopia, particularly in the Amhara region ( 8 , 9 ). The continued civil war in Ethiopia, specifically in the Amhara region, has led to extensive damage to healthcare facilities, disrupting maternal health services for more than 70,000 pregnant women, causing 1.4 million displacements and 600,000 reported deaths ( 11 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on reproductive-aged women indicated the dropout rate for TT was reported at 55.6% (TT1 to TT5). The dropout rates were 5.3% for TT1–TT2, 14.7% for TT2–TT3, 20.2% for TT3–TT4, and the highest, 31.1%, for TT4–TT5 ( 4 , 22 ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation